Laparoscopic repair of vesicovaginal fistula - Wilczyński, Miłosz; Antosiak, Beata; Malinowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2011)
A vesicovaginal fistula is one of the complications that a gynaecologist is bound to face after oncological operations, especially in postmenopausal women. Over the years there have been introduced many techniques of surgical treatment of this entity, including transabdominal and transvaginal approaches. We present a case of a 46-year-old patient who suffered from urinary leakage via the vagina due to the presence of a vesicovaginal fistula that developed after radical abdominal hysterectomy and subsequent radiotherapy. The decision was made to repair it laparoscopically due to retracted, fibrous and scarred tissue in the vaginal apex that precluded a transvaginal approach. A small cystotomy followed by an excision of fistula borders was performed. After six-month follow-up no recurrence of the disease has been noted. We conclude that laparoscopy is an interesting alternative to traditional approaches that provides comparable results.